Teachability in leading organizational mentees: A narrative analysis of reverse mentoring as reflexive moments for coping in personal crisis - Robert Tyler Spradley Ph.D.; James E. Towns Ph.D. (Journal of Human Services: Training, Research, and Practice, 2016)
Mentoring is often situated in leadership and coaching literature as a formal, strategic and a beneficial experience. Additional, studies indicate that mentor/mentee relationships can cause tension and even workplace harassment. Most of these studies focus on the power, whether negative or positive, of the leader versus the mentored. This study synthesizes stories lived and stories told using narrative analysis to balance how reverse mentoring simultaneously assists mentors and mentees in making sense of complex communication environments. Highlighting teachability as a chief characteristic of leading, reverse mentoring co-constructs new narratives for both mentor and mentee to cope with crisis situations. Reciprocal openness to divergent perspectives lends itself to moments in which stories merge and cross to influence both organizational leader and mentee. Thus, bottom-up power is present, not only in follower resistance, but in follower and/or protégé influence in the co-constructing of new organizational and personal narratives.